Experimental Test Works of Water Cleaner for Dust Air Flow in Pipes Out of Cotton Factories - Saidova Nozima A`lovidinovna; Saidova Nozima A`lovidinovna (Scientific Trends, 2025)
The article studies the composition, temperature and velocity of dusty air emitted from cotton ginning plants through practical research, and presents information on the design of a new improved unit with high cleaning efficiency and its advantages, using the temperature and velocity of dust, in accordance with the elements contained in the dust. Using the designed new design, it was experimentally tested in production and recommended for use in cotton factories.
Keywords: Dusty air, cyclone, dust particles, cotton gin, machine units, dusty air flow, aggregate, mineral and organic substances, minerals, atmosphere, environment, pipe, dusty air temperature, dusty air velocity.